Altruism as a Pedagogical Category - Ridkodubska, Anna (Pedagogical Discourse, 2014)
The article examines the philosophical, social and psychological-pedagogical research on the development the idea of altruism. It is established that the introduction of the term «altruism» is associated with the study of selfishness as a social phenomenon and was first proposed by O. Comt, who explained this principle is the idea of «Live for others». During the consideration of the essence personal characteristics of altruism the author reveals his identify and analyze the approaches of various scientists associated with different emphasis on cognitive, motivational, and behavioral components of altruism. In the philosophy of altruism is understood as a category of ethics that opposed selfishness. In psychology the problem of altruism studied in the context of moral development as a holistic personal characteristic. Today the term explain altruism as a moral principle, which involves selfless service to others and a willingness to surrender their sake. Although the term «altruism» has a certain way unstable meaningful feature, you can mark it blurriness in the absence of a clear generalization of the essence of altruism as a special phenomenon, scientifically grounded approach to the characterization of the concept already exists in the Ukrainian and foreign science ideas of apresjan. Beh,Vygotsky L., Tazun I., Korff, M., Rubinstein, S., S. Rusova, Sagach, Sukhomlinsk and other researchers discovered the basic provisions on cultural-historical conditions of the formation and development of foreign and Ukrainian pedagogical systems. We believe that altruism is not a momentary act of manifestation, expression of personality, its position as a permanent solution subject to the problems of his life, even in the absence of vyrazitelnyh forms of action, behavior